Low-value care in nursing: A systematic assessment of clinical practice guidelines. (November 2018) - Verkerk, Eva W.; Huisman-de Waal, Getty; Vermeulen, Hester; Westert, Gert P.; Kool, Rudolf B.; van Dulmen, Simone A.
Abstract: Background: Low-value care provides little or no benefit to the patient, causes harm and wastes limited resources. Reducing it is therefore important for safer and more sustainable care. Objectives: We systematically assessed nursing low-value care practices in Dutch clinical practice guidelines with the aim to facilitate and stimulate nurses to reduce this low-value care. Methods: We screened Dutch clinical practice guidelines for do-not-do recommendations stating that specific nursing care should be avoided. We combined similar recommendations and categorized them by specialism-related groups of nurses, the settings where care took place, and the kind of care according to the Fundamentals of Care framework. Results: We found 66 nursing do-not-do recommendations in 125 clinical practice guidelines, for example, 'Do not use physical restraints in case of a delirium'. Most recommendations were relevant for intensive care nurses (n = 23) and the hospital care setting (n = 49). The majority of recommendations concerned the element safety, prevention and medication of the Fundamentals of Care framework (n = 38). Conclusions: This is the first systematic assessment of low-value nursing care in clinical practice guidelines. The majority of the 66 low-value care practices are not mentioned in other low-value care lists and are therefore new targets for de-implementation. The next step to reducing low-value care should be to create awareness amongst nurses, stimulate the dialogue on de-implementation in practice and facilitate quality improvement projects to quantify and reduce nursing low-value care.